Hands-On Training for Physics Teachers: Project-Based Learning with Solar Energy Systems - Indrasari, Widyaningrum; Fauzi Bakri; Handjoko Permana; Dewi Muliyati; Ahmad Zatnika Purwalaksana; Dadan Sumardani; Achmad Fadhlih Saldy Saputra; Dila Sabila; Iip Wahyuni; Shak Rhuk Khan (Prosiding Seminar Nasional Pengabdian Kepada Masyarakat, 2025)
Abstract This community service program was designed to enhance the pedagogical and technological competencies of physics teachers in MGMP Fisika Jakarta by introducing them to sensor and microcontroller-based learning media. The training consisted of eight structured sessions, beginning with an introduction to microcontroller fundamentals and various types of sensors, including their working principles and real-world applications in physics education. Participants then engaged in hands-on training on operating microcontrollers and constructing measurement instruments, such as temperature and distance sensors, integrated into microcontroller systems. Teachers were also guided through the process of developing simple, sensor-based educational devices tailored to classroom use. To support effective implementation, the training included the creation of a practical guidebook and the production of demonstration videos that could be used in future instruction. Futhermore, participants learned how to build and utilize a Learning Management System (LMS) using Moodle to digitize and manage learning content. The training was delivered through a collaborative, workshop-based approach that encouraged active participation and creativity. As a result, teachers not only improved their technical skills but also gained the ability to integrate technology into physics instruction in innovative ways. The program demonstrated that equipping teachers with skills in sensor and microcontroller technology can significantly enrich STEM-based teaching and learning experiences. AbstrakProgram pengabdian kepada masyarakat ini dirancang untuk meningkatkan kompetensi pedagogik dan teknologi guru fisika di MGMP Fisika Jakarta melalui pengenalan media pembelajaran berbasis sensor dan mikrokontroler. Pelatihan terdiri dari delapan sesi terstruktur, dimulai dengan pengenalan dasar-dasar mikrokontroler serta berbagai jenis sensor, termasuk prinsip kerjanya dan penerapannya dalam pembelajaran fisika. Peserta kemudian mengikuti pelatihan praktik langsung mengenai pengoperasian mikrokontroler dan pembuatan alat ukur seperti sensor suhu dan jarak yang terintegrasi dengan sistem mikrokontroler. Para guru juga dibimbing dalam mengembangkan perangkat edukatif sederhana berbasis sensor yang disesuaikan untuk penggunaan di kelas. Untuk mendukung implementasi yang efektif, pelatihan mencakup pembuatan buku panduan praktis dan produksi video demonstrasi yang dapat digunakan dalam pembelajaran di masa mendatang. Selain itu, peserta belajar cara membangun dan memanfaatkan Learning Management System (LMS) menggunakan Moodle untuk mendigitalisasi dan mengelola konten pembelajaran. Pelatihan ini diselenggarakan dengan pendekatan kolaboratif berbasis lokakarya yang mendorong partisipasi aktif dan kreativitas. Hasilnya, para guru tidak hanya meningkatkan keterampilan teknis, tetapi juga memperoleh kemampuan untuk mengintegrasikan teknologi ke dalam pembelajaran fisika secara inovatif. Program ini menunjukkan bahwa membekali guru dengan keterampilan teknologi sensor dan mikrokontroler dapat secara signifikan memperkaya pengalaman pembelajaran dan pengajaran berbasis STEM.